The Relationship Of Elderly Exercise With Decrease Rheumatoid Arthritic Pain Scale In The Elderly At UPT PS Elderly Binjai-Province Social Office North Sumatra Year 2021 - Asrianti Lase (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2022)
Elderly is someone who has reached the age of 60 years and over. People who are elderly (elderly) will experience a decrease in the ability of body tissues to repair themselves. In addition, being included in the elderly group can cause various health, psychological, and socio-economic problems. One of the health problems that often occurs in the elderly is rheumatoid arthritis. Rheumatoid arthritis (RA) is a chronic, multisystemic inflammatory immune-mediated disease characterized by articular and extra-articular manifestations along with systemic manifestations in the form of malaise and fatigue leading to pain. One of the efforts to reduce rheumatoid arthritis pain is by giving elderly exercise. The purpose of this study was to determine whether there was a relationship between elderly exercise and a decrease in the rheumatoid arthritis pain scale in the elderly. Methods: This study uses descriptive analytic with a cross sectional approach with the number of respondents as many as 40 people with purposive sampling technique sampling. The instrument or tool used is a questionnaire. Results: The results of statistical tests using the chi-square test showed that there was no relationship between elderly gymnastics and a decrease in the rheumatoid arthritis pain scale in the elderly at UPT Binjai Social Services, North Sumatra Province Social Service in 2021.